DRONE, MISSILE, DAN PROXY WAR: STRATEGI BALANCE OF THREAT IRAN DALAM PEPERANGAN MODERN PADA KONFLIK IRAN–ISRAEL - Parhan Pratama Junaedi; Prilla Marsingga (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study analyzes Iran's Balance of Threat strategy in the Iran–Israel conflict through the use of drones, missiles, and proxy warfare within the context of modern warfare. Using Stephen M. Walt's Balance of Threat theory, this research examines how Israel is perceived by Iran as a strategic threat based on four indicators: aggregate power, geographic proximity, offensive capability, and offensive intentions. The study employs a qualitative descriptive approach through literature research using secondary data from academic journals, books, international security reports, and policy documents. The findings indicate that Iran responds to Israel's military superiority by developing drone warfare, missile warfare, and proxy networks as forms of balancing strategy. Drones provide cost-effective surveillance and strike capabilities, missiles function as deterrence instruments against external threats, while proxy groups such as Hezbollah, Hamas, and the Houthis enable Iran to expand its strategic influence without direct military confrontation. The study concludes that drones, missiles, and proxy warfare constitute the three main pillars of Iran's Balance of Threat strategy and reflect the transformation of modern warfare from conventional interstate conflict toward technology-driven and network-based warfare involving both state and non-state actors. Keywords: balance of threat; Iran–Israel conflict; drone warfare; missile warfare; proxy war.   Abstrak: Penelitian ini menganalisis strategi Balance of Threat Iran dalam konflik Iran–Israel melalui penggunaan drone, misil, dan proxy war dalam konteks peperangan modern. Dengan menggunakan teori Balance of Threat Stephen M. Walt, penelitian ini mengkaji bagaimana Israel dipersepsikan Iran sebagai ancaman strategis berdasarkan empat indikator utama, yaitu aggregate power, geographic proximity, offensive capability, dan offensive intentions. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi literatur yang bersumber dari jurnal ilmiah, buku, laporan lembaga keamanan internasional, dan dokumen kebijakan. Hasil penelitian menunjukkan bahwa Iran merespons superioritas militer Israel melalui pengembangan drone warfare, missile warfare, dan jaringan kelompok proksi sebagai strategi balancing. Drone memberikan kemampuan pengintaian dan serangan dengan biaya yang relatif rendah, misil berfungsi sebagai instrumen deterrence terhadap ancaman eksternal, sedangkan kelompok proksi seperti Hezbollah, Hamas, dan Houthis memungkinkan Iran memperluas pengaruh strategisnya tanpa terlibat dalam perang terbuka. Penelitian ini menyimpulkan bahwa drone, misil, dan proxy war merupakan tiga pilar utama strategi Balance of Threat Iran serta mencerminkan transformasi peperangan modern yang semakin berbasis teknologi dan jaringan aktor negara maupun non-negara. Kata kunci: balance of threat; konflik Iran–Israel; drone warfare; missile warfare; proxy war.